Própolis na dieta de abelhas Apis mellifera L. e seu efeito no sistema imune, expressão de genes após o desafio bacteriano e detoxificação frente ao agroquímico Fipronil - Souza, Edison Antônio de [UNESP] (2015)
The Apis mellifera bees may be subject to a number of threats as parasites and pathogens that affect your immune system. This fact makes it necessary to look for natural products that can contribute to improving the immune system of these insects such as propolis. Given the above, the objective was to analyze the influence of the supply of propolis in gene expressions related to immunity of Apis mellifera L. bees subjected to bacterial challenge Over 30 days, four hives receive weekly treatments with different percentages of alcoholic extract of propolis 30% (0%, 5%, 10%, 15%). The experiment was randomized in a factorial 4 x 2 x 2x 3 (treatments x with or without bacteria x times x periods), totaling 48 samples. It was observed the expressions of abaecin, hymenoptaecin, apidaecin and defensing1 genes. As internal control was used actin gene. The results were compared by ANOVA followed by Tukey test (P <0.05). Alterations were observed in gene expression of bees studied for all periods and treatments before and after bacterial challenge for all proposed genes, were yet verified inductions of relative expression in the three periods. It is concluded that under the conditions of this study, propolis can induce the relative expression of genes abaecin, hymenoptaecin, apidaecin and defensin1, when subjected to bacterial challenge. However, it is not able to characterize a treatment with propolis presenting greater relative expression for all genes simultaneously.